#TITLE_ALTERNATIVE# - RACHMAWATI (NIM 17304048), VIERA
Cultural Center is an institution built by certain country in another country in purpose to promote, to socialize, and to give information about the founder country to the society where the institution is built. Scandinavian Cultural Centre is an institution under the Scandinavian countries Embassies, which the mission is to promote, to socialize, and to give information about Scandinavian cultures to Indonesian society where its built. In its effort to achieve its goal, Scandinavian Cultural Center runs programs that are supported the society to increase their knowledge or purposed to manage the activities of Scandinavian Cultural Centre. In order to support all of the Scandinavian Cultural Centre program activities, so the supporting facilities are needed. The priority in designing Scandinavian Cultural Centre is to make the digital library due to its high requirement in technical and esthetical aspects. The supporting facilities for the digital library and other facilities are not as complicated as the digital library but those are still having the same consideration. The main problem in designing Scandinavian Cultural Centre is how to build the image of Scandinavian that different from other country, which is surrounding that region. It has needed to be solved because the countries around Scandinavian region have similarity in their culture developing and also same era with Scandinavian countries is almost every aspect. The consideration in determining design concept such as space planning concept, material concept, color concept, furniture concept, technical concept, and security concept are determined by its function, needs, design theme, and image concept of Scandinavian Cultural Centre.